Prototype Design of Water Treatment Equipment Domestic Waste - Ivonda Vicana Pandang; Sinung Rahardjo; Djumbuh Rukmono (International Journal Labs, 2023)
A prototype design for domestic wastewater treatment has been carried out using the concept of filtration, in which this prototype consists of 2 filters to treat domestic wastewater, the first filter uses a 10-inch cartridge filter media in which filter materials are composed, namely cotton, ferrite, and activated carbon. Then the second filter uses an RO 75 GPD filter which consists of a hollow fiber membrane and has pores of 0.0001 microns. Domestic wastewater from the input reservoir is pumped through the PVC and into filter 1, namely the carbon filter media inside the cartridge filter, the produced water is passed through the ferrite filtration media and then inserted into the membrane, the produced water enters the membrane and RO filter then produces processed wastewater that has been clean and enter into the output reservoir. The results of the functional test explained that the flow velocity of treated wastewater passing through the ¾ inch connecting pipe was 0.22 m/s or 0.24 m3/hour and it took 2 hours to fill an aquarium with a water capacity of 57 liters.